Country Partnership Framework the Arab Republic of Egypt for the Period FY2015-2019 - World Bank Group (World Bank, Washington, DC, 2015)
The World Bank Group (WBG) Country Partnership Framework (CPF) for Egypt forFY15-19 has been prepared at an important juncture in Egypt’s history to support transformational changes to the economic and social space. It builds on the Government of Egypt’s (GOE) medium-term strategy and national priorities for economic development, responds to client demands, and is informed by consultations with a broad array of stakeholders in Egypt. At the same time, the CPF proposes selective interventions in line with the development priorities of the Systematic Country Diagnostic (SCD) for Egypt, and draws on the WBG’s comparative advantage. This program will also seek to implement the new MENA Regional strategy, especially the pillars on renewing the social contract, supporting economic recovery, and promoting regional cooperation. The CPF supports a transformative program to renew the social contract to support private sector job creation, social inclusion, and enhanced governance. The WBG is moving towards more than doubling its lending program compared to the recent past, to a total of about $8 billion over FY15-19, of which an indicative amount of about $6 billion is requested by the authorities to come from IBRD and about $2 billion from IFC. The actual volume and pace of IBRD lending will dependon the implementation of the program, including the ability to address macroeconomic risks, choice of instruments and economic performance in the course of the CPF period, continued Government interest in IBRD financing, and on IBRD’s lending capacity and demands from other borrowers. Similarly, the actual investments by IFC and guarantees by MIGA during the CPF period will depend on improvements in macroeconomic stability and progress in investmentclimate reforms that would boost investor confidence and facilitate greater private sector participation.